2009
DOI: 10.1002/app.30306
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization of a pectin/calcium matrix containing a large fraction of calcium chloride: Implications for sigmoidal release characteristics

Abstract: The physicochemical properties of pectin/ calcium matrix tablets were studied with an emphasis on the effect of over 50% of calcium chloride to better understand the fundamentals of the drug-release mechanisms. The absence of the adsorption of methylene blue onto the calciumcontaining pectin matrix served as evidence of the calciumion-induced in situ crosslinking of pectin chains. Visual and scanning electron microscopy observation showed the reinforced robustness of the pectin/calcium matrix, whereas cryo-SEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In previous study, we reported that fortification of pectin gels could be achieved via calcium cation-induced in situ crosslinking (Wei et al, 2006(Wei et al, , 2009Wu et al, 2007a;Wu et al, 2008). Consequently, significant slowing of the initial drug release and a sigmoid release pattern were observed with use of these pectin/calcium chloride (P/Ca) matrix systems.…”
Section: Introductionmentioning
confidence: 99%
“…In previous study, we reported that fortification of pectin gels could be achieved via calcium cation-induced in situ crosslinking (Wei et al, 2006(Wei et al, , 2009Wu et al, 2007a;Wu et al, 2008). Consequently, significant slowing of the initial drug release and a sigmoid release pattern were observed with use of these pectin/calcium chloride (P/Ca) matrix systems.…”
Section: Introductionmentioning
confidence: 99%
“…Consistency is highly dependent on crosslinking of pectin with divalent cations such as calcium (Slavov et al 2009;Wei et al 2009;Yoo et al 2009). However, the fact that the treatments with 0.5% w/w and 1% w/w of NovoShape™ increased tomato paste consistency throughout 3 hrs of assay (P < 0.05) without addition of divalent cations suggests that consistency is not limited by these elements in tomato paste, which can be observed in Figure 1a and c.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, pectin can be used in the pharmaceutical field owing to its good biocompatibility [ 1 , 2 , 3 ]. For example, pectin can be crosslinked with calcium ions, which is a suitable delivery system to escort drugs from the mouth to the colon [ 4 , 5 ]. On the other hand, chitosan and chitosan hydrochloride chitosan ( Scheme 2 ) are cationic polysaccharide polymer derived from chitin, which can be found in the shells of shrimp, crabs, lobsters, etc.…”
Section: Introductionmentioning
confidence: 99%